2017
DOI: 10.1055/s-0037-1606568
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA as Thrombosis Sentinels: Caveats and Considerations

Abstract: The small noncoding RNAs, microRNAs (or miRNAs), have been implicated in a myriad of diseases and accumulating evidence indicate their potential high value as diagnostic biomarkers. Although their roles in hemostasis and coagulation pathways are less defined, many studies have demonstrated their participation in regulating key factors of hemostasis. However, the mounting challenges associated with the accurate measurement of circulating miRNAs and the involvement of platelet activation in contributing to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 114 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…Multiple events of MACCE (such as venous thromboembolism, coronary artery disease, and ischemic stroke) are mainly caused by thrombosis that is a consequence of the disrupted equilibrium between pro-coagulation and anticoagulation [8,17,18]. In order to decrease the MACCE risk and the related mortality in CAPD patients, mounting studies are performed and they reveal that miRNAs have been identified as the regulators in various physiological functions and pathological conditions, including coagulation process [8,14,[17][18][19]. According to previous data, miRNAs might participate in coagulation mainly through the following mechanisms: (1) directly targeting hemostatic factors (such as fibronectin (FN1) and fibrinogen β chain (FGB));…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple events of MACCE (such as venous thromboembolism, coronary artery disease, and ischemic stroke) are mainly caused by thrombosis that is a consequence of the disrupted equilibrium between pro-coagulation and anticoagulation [8,17,18]. In order to decrease the MACCE risk and the related mortality in CAPD patients, mounting studies are performed and they reveal that miRNAs have been identified as the regulators in various physiological functions and pathological conditions, including coagulation process [8,14,[17][18][19]. According to previous data, miRNAs might participate in coagulation mainly through the following mechanisms: (1) directly targeting hemostatic factors (such as fibronectin (FN1) and fibrinogen β chain (FGB));…”
Section: Discussionmentioning
confidence: 99%
“…miR-92a-3p, which belongs to the miR-17-92 cluster, is identified as a blood coagulation related miRNA that associated with disease risk of some cardiovascular diseases [11,14,20,21]. For instance, a study shows that miR-92a-3p expression were downregulated in blood samples of congestive heart failure patients compared to healthy controls [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MicroNRAs are short non‐coding RNAs that have been identified with crucial roles in venous thrombosis . Besides, microRNAs play an important role in the modulation of stem cells and angiogenesis .…”
Section: Introductionmentioning
confidence: 99%